New species and new records of Tingidae (Hemiptera: Heteroptera) from Vietnam - Guilbert, Eric (Zootaxa, 2015)
Tingidae (Hemiptera: Heteroptera) collected in Vietnam by several institutions between 1958 and 2013 continue to yield new information about tropical diversity in this family of insects. Herein, thirty-seven species are newly recorded for Vietnam, and four are described as new to science. Comments on their affinities and distribution are provided, highlighting the biological richness of a rapidly developing country with human impacts.